Property Tax Systems in Selected European Union Countries and the Proposed Tax Reform in Poland - Laskowska, Elwira (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
The purpose of this article is to compare the property tax systems applied in the European Union countries in the context of the proposed tax reform in Poland. In addition, an attempt was made at identifying the advantages and disadvantages of this reform. The results of the analyses allow us to conclude that the experience of the countries where the cadastral property taxation system is applied corroborates the validity of introducing such a system in Poland. The importance of the cadastral property tax in terms of budgetary revenues in individual EU countries varies because of the different way of determining the so-called property tax value (the tax value of the real estate). Nevertheless, determination of the tax in relation to the value of the property will allow for a more equitable distribution of the tax burden, especially with the application of a tax relief and preference system for taxpayers. The related literature exposes certain social unrest associated with the increase of the tax burden due to the introduction of the cadastral tax. However, it should be noted that, as a consequence, such burden will be correlated with the financial situation of the taxpayer. In addition, the possible increase in the tax revenues paid to the local government budgets is hardly a negative effect of the proposed tax reform, while the high cost of the creation of cadastre, perceived as a disadvantage, is a natural consequence of economic changes in the country, in particular, in the case of justified future benefits.